Telaah Manajemen Sumber Daya Manusia Berbasis Al-Qur’an Surah Al-Baqarah Ayat 267 dalam Penguatan Ekonomi Umat Berbasis Syariah - Komarudin, Udin; Maulin , Mery; Fathonih, Ah.; Dea, Dea (STAI Al-Musaddadiyah Garut, 2025)
This study aims to explore the role of Islamic Economic Law in providing solutions to the problem of unemployment in Mekarsari Village, Cilawu District, Garut. Unemployment is a significant challenge that hinders economic growth and community welfare in the area. Through a practical approach, this research identifies the implementation of Islamic economic principles in local economic activities, such as zakat, waqf, and sharia-based financing, which can create job opportunities. A theoretical approach is used to analyze relevant sharia concepts in the context of addressing unemployment. The research method employed is qualitative, with data collected through in-depth interviews, observation, and document analysis. The results show that the application of Islamic Economic Law, through community empowerment programs and sharia-based business development, can significantly reduce unemployment rates, strengthen MSMEs, and improve the welfare of the people in Mekarsari Village. This study is expected to contribute to the development of more effective sharia economic policies at the local level. Keywords: Law, Islamic Economics, Unemployment, Community Empowerment;